Estimating σ-meson couplings from D→3π decays - Dib, Claudio; Rosenfeld, Rogerio (American Physical Society (APS), 2001)
Using recent experimental evidence from E791 on the sigma meson in D→3π decays, we study the relevant couplings in D→σπ and σ→ππ within the accepted theoretical framework for nonleptonic D decays, finding an overall consistency of the theory with the experimental data. ©2001 The American Physical Society.